Analysis of the Effect Construction Costs, Human Development Index and Investment: Does It Have an Impact on Economic Development? - Prince Charles Heston Runtunuwu; Muhammad Kotib (AIBPM Publisher, 2021)
The purpose of this study aims to investigate a causality relationship between Construction Cost Index (CCI) and economic growth, between investment and economic growth, and between human development index and economic growth in North Maluku Province. With the error correction model approach, this study was carried out with the Granger causality method. The findings indicate that the economic growth and the Construction Cost Index affected the value of economic growth significantly. While the value change in the Construction Cost Index is statistically insignificant to affect the value of Economic Growth implying no causality relationship between the variables of Construction Cost Index to economic growth. There is only a one-way relationship, namely economic growth affecting the Construction Cost Index . Economic growth and investment have an association to changes in the value of economic growth significantly affecting the value of Investment. Humans do not have a causality (causal) relationship affecting each other or the Human Development Index (HDI) has no chance of being a dependent variable in the quarter of 2010 to 2019.